Neuroimaging findings in midlife and risk of late-life dementia over 20 years of follow-up. (26th February 2019) - West, Nancy A.; Windham, B. Gwen; Knopman, David S.; Shibata, Dean K.; Coker, Laura H.; Mosley, Thomas H.
Abstract : Objective: To examine the association between neuroimaging features in a predominantly middle-aged cohort and risk of late-life dementia. Methods: Cerebral MRI was performed on 1, 881 individuals with no history of stroke from the Atherosclerosis Risk in Communities Study cohort in 1993 to 1995. White matter hyperintensities (WMH), ventricular size, and sulcal size were graded on a semiquantitative scale, and presence of silent cerebral infarcts was identified. In 2011 to 2013, dementia was determined from neuropsychological testing, informant interview, hospital ICD-9 codes, and death certificate dementia codes. Cox regression was used to evaluate associations between MRI findings and dementia. Results: Over 20 years of follow-up, dementia developed in 279 participants (14.8%). High-grade WMH and high-grade ventricular size were independently associated with increased dementia risk (hazard ratio [HR] for WMH 1.62, 95% confidence interval [CI] 1.14–2.30; HR for ventricular size 1.46, 95% CI 1.06–2.03). There was an increased risk of dementia for diabetic participants with silent infarcts (HR 2.56, 95% CI 1.23–5.31) but not among nondiabetic participants (HR 0.87, 95% CI 0.56–1.37). Each 1-unit increase in the total number of high-grade cerebral abnormalities at baseline (count values range 0–4) showed increased dementia risk, with a considerably higher risk among diabetic participants (HR for diabetes mellitus 1.97, 95% CI 1.44–2.69; HR for no diabetes mellitus 1.20, 95% CI 1.03–1.39). Conclusion: In adults without evidence of clinical stroke, MRI-detected WMH and ventricular enlargement in midlife may represent markers of brain injury that increase risk for later-life cognitive impairment. The presence of diabetes mellitus may modify the association between silent infarcts and dementia.